Disability Disclosure in the Workplace - Wilton, Robert D. (Just Labour: A Canadian Journal of Work and Society, 2006)
This paper is concerned with workplace accommodation and the extent to which people feel able to disclose disabilities at work. Disclosure is central to accommodation in the sense that workers must feel comfortable describing their needs to employers. Where this is not the case, for example, where workers are concerned about the precariousness of their position and the fact that disclosure may result in dismissal, legal requirements for accommodation can be ineffective. To explore this issue, the paper uses qualitative data from interviews with fifty-nine people with physical, learning, psychiatric and sensory disabilities in the Hamilton labour market. Analysis indicates that most respondents viewed disclosure as a risky endeavour, and a significant minority did not disclose due to concerns about not being hired or being dismissed. The conclusion discusses the need for accommodating workplaces and the implications for the labour movement.